2014
DOI: 10.1016/j.jallcom.2013.10.052
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a micro-porous Ti–Zr alloy by electroless reduction with a calcium reductant for electrolytic capacitor applications

Abstract: A metallic titanium and zirconium micro-porous alloy for electrolytic capacitor applications was produced by electroless reduction with a calcium reductant in calcium chloride molten salt at 1173 K. Mixed TiO 2 -70at%ZrO 2 oxides, metallic calcium, and calcium chloride were placed in a titanium crucible and heated under argon atmosphere to reduce the oxides with the calcium reductant. A metallic Ti-Zr alloy was obtained by electroless reduction in the presence of excess calcium reductant and showed a micro-por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 29 publications
1
12
0
1
Order By: Relevance
“…In a previous investigation, we observed that excess calcium reductant caused the complete reduction of titanium and zirconium oxides. The details of the reduction setup used in the present investigation have been described elsewhere [44].…”
Section: Reduction Of Titanium Oxidementioning
confidence: 99%
See 2 more Smart Citations
“…In a previous investigation, we observed that excess calcium reductant caused the complete reduction of titanium and zirconium oxides. The details of the reduction setup used in the present investigation have been described elsewhere [44].…”
Section: Reduction Of Titanium Oxidementioning
confidence: 99%
“…Very recently, the authors have investigated the fabrication of a metallic titanium and zirconium micro-porous alloy by reduction with a calcium reductant in calcium chloride molten salt for novel electrolytic capacitor applications [44]. It is known that defect-free, high-capacitance composite anodic oxide films can be formed on substrates by anodizing a Ti-62.5 at% Zr alloy [45][46][47][48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Titanium and titanium alloy powders can also be produced by an indirect electrochemical reduction process of the relative oxides in molten CaCl 2 -CaO, namely, the well-known O-S (Ono-Suzuki) process 16,17) . For example, TiZr 18) , TiNbNi 19) as well as a biomedical alloy, Ti-29Nb-23Ta-4.6Zr (TNTZ) 20) with very low oxygen content were prepared by the method. Compared with other methods, the direct and indirect molten-salt electrochemical reduction methods only contain one step without merging the metal extraction and melting process, resulting in a lower energy consumption, i.e., 23.5 kWh/kg-TiNi alloy 21) and possibly low cost.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Various transition metals can be directly reduced from their oxides with metallic calcium because of its strong reducing ability. Therefore, calciothermic reduction for industrial applications had been widely investigated by many research groups to date, and metallic titanium, 4-9 zirconium, 10,11 hafnium, 12 niobium, [13][14][15] tantalum, 16,17 nickel, 18 uranium, 19 and their alloys [20][21][22][23][24][25][26][27] can be successfully obtained via calciothermic reduction and advanced techniques. 28,29 Although carbon dioxide (CO 2 ) is an extremely stable chemical species in our environment, the chemical decomposition of CO 2 is an important technology for global environmental issues.…”
mentioning
confidence: 99%